KUALITAS HIDUP ANAK USIA 3-5 TAHUN DENGAN EARLY CHILHOOD CARIES YANG TIDAK DITANGANI - Abu Hamid; Dhandi Wijaya; Zainur Sulaiman; Ismalayani Ismalayani (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
Early childhood caries (ECC), dental caries affecting the primary teeth in preschool aged children, is prevalent, especially among low social economic groups in developing countries. Treatment of ECC in developing country is almost nonexistent, so that it can cause more serious complications ((pulpitis, ulceration, fistula, and abscess). Untreated ECC can affect on quality of life in preschool aged children.This cross-sectional study aim was to evaluate association between untreated ECC and quality of life of preschool children (aged 3-5 years). This study was conducted on September until October 2018 in playgroups or kindergartens in Ilir Barat I Subdistrict, Palembang and consisted of 334 preschool children–parent pairs.Untreated ECC was assessed by PUFA/pufa index and preschool children’s quality of life by ECOHIS instrument. Association between untreated ECC and preschool children’s quality of life were analyzed using the Fisher’s exact test with 95% CI.The result showed that ECC prevalence was 84.1% dan more than 90% was untreated ECC. The pufa was developed in 39.1% untreated ECC. There wasa significant association between untreated ECC and preschool children’s quality of life (p0,05).